ABC of green infrastructure analysis and planning: the basic ideas and methodological guidance based on landscape ecological principle - Thian, Owen Seng Yeo; Mohd Yusof, Mohd Johari; Maruthaveeran, Sreetheran; Mohd Shafri, Helmi Zulhaidi; Saito, Kei; Lee, Bak Yeo (Elsevier, 2022)
Green infrastructure (GI) is a pivotal multifunctional approach for urban green spaces fragmentation problem. The green space fragmentation issue has increasingly caught worldwide researchers’ critical attention. However, researchers face challenges in understanding GI analysis and planning. Only limited research exists on GI analysis and planning case studies. Therefore, this study reviewed case studies on GI analysis and planning. The finding simplifies GI analysis and planning case studies methodology and critical points to get more worldwide researchers’ attention. The study applied a systematic literature review (SLR) on 34 qualified studies to determine the trends and similarities of GI case studies. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2009) was adopted for the study. The review found a sequential methodological pattern in GI analysis and planning study. The review themes were trend analysis, basic study information, study nature, geographic information system (GIS) software and plugin, remote sensing processing and data needed, and analysis and output. Thus, the study provides a basic methodology and framework for developing GI analysis and planning based on the landscape ecology principle.